2010
DOI: 10.1111/j.1479-8298.2010.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Subterranean species of the ant genus Crematogaster in Asia (Hymenoptera: Formicidae)

Abstract: Three Crematogaster ant species, C. (Orthocrema) javanica Menozzi, C. (O.) myops Forel and C. (O.)masukoi sp. nov., share reduced compound eyes which characterizes them among Asian species of the subgenus Orthocrema. The new species is described based on material from Borneo. It can be distinguished from C. javanica and C. myops by its smooth surface of clypeus and acutely produced subpetiolar process. Reduced compound eyes and yellowish body suggest that these three species are subterranean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 5 publications
(12 reference statements)
0
22
0
Order By: Relevance
“…myops have reduced compound eyes (approximately 6–10 ommatidia) and depigmented yellowish bodies. The two species are similar in that they have reduced eyes, but they are quite different from each other in other morphological aspects (Hosoishi et al ., ). Our cladistic analysis showed that C .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…myops have reduced compound eyes (approximately 6–10 ommatidia) and depigmented yellowish bodies. The two species are similar in that they have reduced eyes, but they are quite different from each other in other morphological aspects (Hosoishi et al ., ). Our cladistic analysis showed that C .…”
Section: Discussionmentioning
confidence: 97%
“…Hosoishi et al . () revised the subterranean species from the Asian Orthocrema fauna. Crematogaster masukoi and C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently regional taxonomic revisions of the genus or subgenera have been conducted (Buren, 1959;Buren, 1968;Longino, 2003;Hosoishi & Ogata, 2009;Blaimer, 2010;Blaimer, 2012b;Blaimer, 2012c;Blaimer, 2012d;Hosoishi & Ogata, 2012;Blaimer & Fisher, 2013;Hosoishi 2015). While the genus itself is morphologically clearly defined by the dorsal attachment of the postpetiole to the first gaster segment (Bolton, 1994;Blaimer, 2012b), the formerly used subgenera were based on vague characters only.…”
Section: Taxonomy Of the Genus Crematogastermentioning
confidence: 99%